ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI MENGIKUTI PPG MANDIRI PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Dona Tila Beni Yanti; F.Y. Khosmas; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
ABSTRACTThis study aimed to determine the factors that influence motivation to follow the independent teacher professional education in the 2014 and 2015 batch of economic education students of the Teaching Training and Education Faculty of Tanjungpura University. The research method used was descriptive qualitative research form. The data source of this study was the 2014 batch of economic education students that consist of 2 people and 12 people of batch 2015 economic education students and the data were factors influencing the motivation to follow the independent teacher professional education and the results of interviews with the 2014 and 2015 batch of economic education students. the results of the research showed that motivation from internal factors interest in following the teacher professional education were assessed as enough, student interest in becoming teachers was considered enough, student's positive attitudes on educator certificates were considered enough, teacher professional education as needs assessed enough, motivation of external factors in family environments was considered enough, friend's environment in motivating was considered enough, community's environment in motivating was considered lacking. Then, it can be concluded that the economic education student motivation was enough. Key words: Independent Teacher Professional Education, Motivation, Students of Economic Education